MicroRNA‐216a/217‐induced epithelial‐mesenchymal transition targets PTEN and SMAD7 to promote drug resistance and recurrence of liver cancer. Issue 2 (25th June 2013) - Xia, Hongping; Ooi, London Lucien P.J.; Hui, Kam M.
<x xml:space="preserve">Abstract</x> Tumor recurrence and metastases are the major obstacles to improving the prognosis of patients with hepatocellular carcinoma (HCC). To identify novel risk factors associated with HCC recurrence and metastases, we have established a panel of recurrence‐associated microRNAs (miRNAs) by comparing miRNA expression in recurrent and nonrecurrent human HCC tissue samples using microarrays (recurrence is defined as recurrent disease occurring within a 2‐year time point of the original treatment). Among the panel, expression of the miR‐216a/217 cluster was consistently and significantly up‐regulated in HCC tissue samples and cell lines associated with early tumor recurrence, poor disease‐free survival, and an epithelial‐mesenchymal transition (EMT) phenotype. Stable overexpression of miR‐216a/217‐induced EMT increased the stem‐like cell population, migration, and metastatic ability of epithelial HCC cells. Phosphatase and tensin homolog (PTEN) and mothers against decapentaplegic homolog 7 (SMAD7) were subsequently identified as two functional targets of miR‐216a/217, and both PTEN and SMAD7 were down‐regulated in HCC. Ectopic expression of PTEN or SMAD7 partially rescued miR‐216a/217‐mediated EMT, cell migration, and stem‐like properties of HCC cells. Previously, SMAD7 was shown to be a transforming growth factor beta (TGF‐β) type 1 receptor antagonist. Here, we further demonstrated that overexpression of miR‐216a/217 acted as a positive feedback regulator for the TGF‐β pathway and the canonical pathway involved in the activation of phosphoinositide 3‐kinase/protein kinase K (PI3K/Akt) signaling in HCC cells. Additionally, activation of the TGF‐β‐ and PI3K/Akt‐signaling pathways in HCC cells resulted in an acquired resistance to sorafenib, whereas blocking activation of the TGF‐β pathway overcame miR‐216a/217‐induced sorafenib resistance and prevented tumor metastases in HCC. Conclusion: Overexpression of miR‐216a/217 activates the PI3K/Akt and TGF‐β pathways by targeting PTEN and SMAD7, contributing to hepatocarcinogenesis and tumor recurrence in HCC. (Hepatology 2013;58:629–641)